SYSTEMIC MECHANISMS OF CHRONIC OPISTHORCHIASIS - N. V. Karbysheva; E. A. Bobrovskij; I. P. Saldan (Журнал инфектологии)
AbstractPurpose: the evaluation of systemic immunobiochemical mechanisms of chronic opisthorchiasis, significant pathogenic criteria for the disease activity degree. Subjects and methods: We studied 312 chronic opisthorchiasis patients with the laboratory-confirmed diagnosis. The functional status of humoral immunity was assessed in 312 patients before the course of treatment and during the residual period of the invasion (2 weeks, 3 and 6 months after the course of treatment) together with the dynamics of specific markers (IgM and IgG antibodies and antigen Op. felineus CICs). According to the course of opisthorchiasis and the treatment provided the levels of autoantibodies to native and denatured DNA antigens were assessed in 94 patients. Results: All patients showed high levels of immune complexes which were circulating in blood during the whole period of the disease, including immune complexes specific to antigen Op. felineus (61.3% of all seropositive results). We revealed a significantly high level of autoantibodies to native and denatured DNA antigens and their destruction was observed for a longer period of time compared to the designated period of follow-up monitoring (during 6 months). The destruction took place irrespective of the course of opisthorchiasis – nonmanifest or manifest. The results show a significant negative correlation between the level of autoantibodies to native and denatured DNA antigens and the amount of immune complexes (r =- 0.48, r = – 0.73). Conclusion: Humoral immune response components are only disease markers during the course of opisthorchiasis and long period of circulation of specific and nonspecific immune complexes and they cause Op.felineus persistence in a host organism. The destruction revealed according to the levels of K nDNA and K dDNA during the whole period of followup monitoring may be one of the symptoms of post-opisthorchiasis even in the case of effective dehelmintization and it may work as an objective criterion for the disease activity degree. The correlation between the levels of autoantibodies to DNA and CICs show that immune mechanisms contribute to the process of the destruction.